‘Nós ainda estamos aqui’ : resistência e autodeterminação indígena na África do Sul - Barros, Rodrigo Ferreira (2023)
In the cases of post-colonial states in the Global South, the struggles of self-declared indigenous communities are some of the most iconic and dramatic claims of legal pluralism and democracy itself. In the case of South Africa, these groups, often referred to as the San and the Khoi, are estimated to account up to 1% of the national population. Despite legal recognition of some of their institutions and some acknowledgement of their presence, it has been considerably difficult for the communities to achieve proper representation in the formal spaces and deliberative stances of politics. Even in the cases that regard their own lands and their specific traditional knowledge they struggle to be considered in the decision-making processes. The historical records of these groups reveal a long history of counter colonial resistance, with strategies of combat and negotiation, focused on their physical and cultural survival until the installment of a democratic order. In order to implement international legislation and national premises of legal pluralism and self-determination, indigenous peoples draft, translate and try to execute self-legislation pieces as exercises of autonomy. Alternatively, there are other indigenous collectives which consider state structures to be inadequate to their interests, and engage in autonomous activities independently of government apparel, focused on the strengthening of their cultures, languages and ways of life.